Analysis of the Implementation of Hotel Tax Collection on Boarding Houses in Depok City in 2018-2021 - Trie Andari Ratna Widyastuti; Dadan Hidayat (Ilomata International Journal of Tax and Accounting, 2022)
Hotel tax on boarding houses is one of the Original Regional Incomes (PAD), which is categorized into Hotel Tax. There are several boarding house owners who do not report and pay for their boarding house business tax, which in this matter does not conform to the regulation related to boarding house tax which is Laws Number 28 of 2009 regarding Regional Rax and Retribution and Regional Regulation of Depok City Number 07 of 2010. The purpose of this study is to find out and analyze the Implementation of the Hotel Tax Collection on Boarding House in Depok City within 2018-2020. The method used in this study is the qualitative method with descriptive research. The result indicates that the Implementation of hotel tax collection on boarding houses in Depok City within 2018-2020 has not yet been implemented well due to the awareness of the taxpayers is still low, the counseling, education, and socialization that has not yet maximum, and the lack of human resource amount who can handle the hotel tax collection on the boarding house.